2015
DOI: 10.1080/ac.70.3.3080639
|View full text |Cite
|
Sign up to set email alerts
|

Women have right ventricular infarction more frequently than men

Abstract: Right ventricular infarctions occur more frequently in women than in men.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 0 publications
0
3
3
Order By: Relevance
“…This finding is consistent with results of Bueno et al 55 No significant differences were observed between inferior MI patients with and without RVI regarding patients' gender. This finding is inconsistent with results of Obradovic et al 57 study in Serbia which confirmed that women were at higher risk of RVI than men.…”
Section: Discussioncontrasting
confidence: 94%
“…This finding is consistent with results of Bueno et al 55 No significant differences were observed between inferior MI patients with and without RVI regarding patients' gender. This finding is inconsistent with results of Obradovic et al 57 study in Serbia which confirmed that women were at higher risk of RVI than men.…”
Section: Discussioncontrasting
confidence: 94%
“…This might be due to the low occurrence of certain other risk factors in this sample of women, like smoking. This finding contradicts the research by Obradovic S, et al of the increased incidence of RVI in females [8]. Our sample of women was from a southeast culture where smoking is less common in the female gender [9].…”
Section: Discussioncontrasting
confidence: 78%
“…In the current study, gender was not significantly associated with right ventricular infarction occurrence. However, a study showed that female patients are at increased risk of right ventricular infarction (Obradovic et al, 2015). In the current study, 49.09% of patients were smokers, and no significant association was found between smoking and the incidence of RVI in patients with inferior wall MI, in contrast to a previous study which reported smoking as a risk factor for right ventricular infarction (Obradovic et al, 2015).…”
Section: Resultscontrasting
confidence: 99%
“…However, a study showed that female patients are at increased risk of right ventricular infarction (Obradovic et al, 2015). In the current study, 49.09% of patients were smokers, and no significant association was found between smoking and the incidence of RVI in patients with inferior wall MI, in contrast to a previous study which reported smoking as a risk factor for right ventricular infarction (Obradovic et al, 2015). In the current study, a significant link was seen between diabetes and the development of RVI in patients with MI.…”
Section: Resultsmentioning
confidence: 99%